Grassland Ecology and Ecosystem Management for Sustainable Livestock Performance - Deidre D. Harmon; Edward B. Rayburn; Thomas C. Griggs (Agronomy, 2023)
Grassland ecosystems differ in plant and animal species composition and appearance depending on the location and climate [...]